Building a Transcendental (Complete) Person by Muhammad Iqbal - Krifif, Boulanouar; tayeb, Kehileche (International Journal of Psychosocial Rehabilitation, 2022)
A person is present in this existence with its sensory and moral dimensions, and when he tries to prove his existence, that is, its effectiveness, he must first establish its sensory and moral meaning, secondly, set his distance with the other one and take himself in the subject as an attempt to understand what he is and set his equation of his existence to achieve his perfection and his integrity and to be a model example that defined himself and our meaning and knew What is his and what is on it and his revelation became a reality, as an activity raging on the ground her soul is returning to the sky, so it was necessary to be pigmented with its dye and like it built its society and even its state as a harmonious cosmic building.